Parent Focused Parentification : Eksplorasi Inversi Peran Anak Sebagai Penopang Emosional dan Fungsional Orang Tua - Saffanah Nur Madina; Neng Wulan Sari; Syahnur Rahman; Joanne Marrijda Rugebregt (Journal of Innovative and Creativity, 2025)
Parent-focused parentification occurs when children take on emotional and functional responsibilities typically held by parents, especially in families facing structural stress such as chronic illness. This study systematically explores this phenomenon in children using a Systematic Literature Review (SLR) with the PRISMA approach. Articles published between 2010 and 2024 were selected from Google Scholar, Scopus, and ScienceDirect using strict inclusion criteria. Data were analyzed thematically and presented in a narrative synthesis. Findings reveal that the effects of parentification depend on role type, family context, and social support. Instrumental parentification can positively influence academic performance when supported by good quality of life. In contrast, emotional parentification is linked to higher risks of stress, depression, and identity issues when lacking adequate support. Tools such as the Parentification Inventory are essential for objectively assessing these experiences. This review underscores the importance of recognizing children's roles in the family and implementing appropriate interventions to prevent negative psychological outcomes and promote healthy adolescent development.